2018
DOI: 10.3892/ijmm.2018.3987
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics-based study to detect chemical compounds that show potential as treatments for pulmonary thromboembolism

Abstract: The objectives of the present study comprised the recognition of major genes related to pulmonary thromboembolism (PTE) and the evaluation of their functional enrichment levels, in addition to the identification of small chemical molecules that may offer potential for use in PTE treatment. The RNA expression profiling of GSE84738 was obtained from the Gene Expression Omnibus database. Following data preprocessing, the differently expressed genes (DEGs) between the PTE group and the control group were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…PE has a high rate of misdiagnosis, missed diagnosis, and mortality in clinical practice. The first venous thromboembolism (VTE) in the United States every year is 100/100,000, of which about 30% develop into PE [ 5 ]. Foreign autopsy statistics have found that the missed diagnosis rate of pulmonary embolism is as high as 67%, and the misdiagnosis rate is as high as 63%.…”
Section: Related Workmentioning
confidence: 99%
“…PE has a high rate of misdiagnosis, missed diagnosis, and mortality in clinical practice. The first venous thromboembolism (VTE) in the United States every year is 100/100,000, of which about 30% develop into PE [ 5 ]. Foreign autopsy statistics have found that the missed diagnosis rate of pulmonary embolism is as high as 67%, and the misdiagnosis rate is as high as 63%.…”
Section: Related Workmentioning
confidence: 99%
“…Search Tool for the Retrieval of Interacting Genes/Proteins (STRING; http://string-db.org/ ) was used to construct interaction networks among the DEGs-coded proteins(setting criteria: medium confidence ≥ 0.9) [ 13 ]. The most significant PPIs were plotted with the application of Cytoscape (v3.7.2, http://cytoscape.org/ ) [ 14 ] and the top module with the highest score (setting: k-core > 2) was identified. The proteins encoded by genes in the same module tended to have the same or analogous functions, and these proteins were enriched for the same biological role [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…If one gene was detected by multiple probes, the mean value of the probes can then represent the expression level [ 7 ]. Gene expression data from the paralytic and concomitant esotropia groups were separated according to the Linear Models for Microarray Data package (LIMMA), and DEGs between the two groups were screened in R software [ 8 ].…”
Section: Methodsmentioning
confidence: 99%